2008
DOI: 10.1590/s0102-86502008000600003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an isolated mild to moderate ischemic brain injury in the gastric emptying of liquids in rats

Abstract: Purpose:To evaluate the effect of hypoxic-ischemic brain injury over the gastric emptying of liquids in rats. Methods: Fifty-two Wistar rats aged six weeks and weighing between 100g and 150g were divided in three groups. A Control group (C), a Sham group (S) undergoing sham procedure, and a Hypoxic-ischemic group (HI) consisting of 18 animals undergoing surgical ligature of the left carotid artery and exposure to hypoxic environment for three hours. Half of the animals were studied in the third day post-HI pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…reported that gastric emptying did not change following mild to moderate ischemic brain injury, which is inconsistent with our results. [ 29 ] Possible reasons for this controversy could be explained by ischemic brain injury type, time and measurement method of gastric motility.…”
Section: Discussionmentioning
confidence: 99%
“…reported that gastric emptying did not change following mild to moderate ischemic brain injury, which is inconsistent with our results. [ 29 ] Possible reasons for this controversy could be explained by ischemic brain injury type, time and measurement method of gastric motility.…”
Section: Discussionmentioning
confidence: 99%